MEASUREMENT OF HEALTH INEQUALITY - NICOLETA CARAGEA (Challenges of the Knowledge Society, 2011)
Health inequality is met everywhere in the world, including in countries with a high level of economic development, or those with strong social protection systems. In this paper I analyzed certain methods to measure health inequalities between population groups and also I presented some empirical results regarding health disparities between European Union countries. My research is focussed on three health areas: health status of population, access to health care services and resource allocation and population spending on health care.